Correlation of Active Sites to Generated Reactive Species and Degradation Routes of Organics in Peroxymonosulfate Activation by Co-Loaded Carbon - Ning Li; Li, Rui; Xiaoguang Duan; Beibei Yan; Liu, Wen; Cheng, Zhanjun; Guanyi Chen; Li’an Hou; Shaobin Wang (Environmental Science & Technology, 2021)
Peroxymonosulfate (PMS)-based advanced oxidation processes (PMS-AOPs) as an efficient strategy for organic degradation are highly dependent on catalyst design and structured active sites. However, the identification of the active sites and their relationship with reaction mechanisms for organic degradation are not fully understood for a composite catalyst due to the complex structure. Herein, we developed a family of Co encapsulated in N-doped carbons (Co-PCN) with tailored types and contents of active sites via manipulated pyrolysis for PMS activation and ciprofloxacin (CIP) degradation, focusing on the correlation of active sites to generated reactive species and degradation routes of organics. The structure–function relationships between the different active sites in Co-PCN catalysts and reactive oxygen species (ROS), as well as bond breaking position of CIP, were revealed through regression analysis and density functional theory calculation. Co–Nx, O–C═O, C═O, graphitic N, and defects in Co-PCN stimulate the generation of 1O2 for oxidizing the C–C bond in the piperazine ring of CIP into C═O. The substitution of F by OH and hydroxylation of the piperazine ring might be induced by SO4•– and •OH, whose formation was affected by C–O, Co(0), Co–Nx, graphitic N, and defects. The findings provided new insights into reaction mechanisms in PMS-AOP systems and rational design of catalysts for ROS-oriented degradation of pollutants.